A biomedically-enhanced body-subject? A critical analysis of the reconcilability of Maurice Merleau-Ponty’s ideas with current-day claims about biomedical enhancement - Gardner, Sarah (Stellenbosch : Stellenbosch University, 2022)
Thesis (MPhil) -- Stellenbosch University, 2022.